Measurement of the Mass Difference Between Neutral Charm-Meson Eigenstates - Aaij R. Roel; Beteta C. A. Carlos Abellan; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich (2019, 2019)
Title screen